Hit the GAS: Designing Optimal Generalized Ad-supported Subscription Mechanisms - Gutt, Dominik; Mehta, Sameer; Quinn, Martin (Information Systems Research, 2026)
Digital Content Platforms (DCPs), such as Netflix and Spotify, rely on subscriptions and advertising as their primary revenue sources. Traditional revenue models, such as subscription-only and ad-only options, either limit user accessibility or compromise user experience. In response, DCPs have started to combine these two models by offering a two-tier menu: a free ad-supported tier for price-sensitive users and a paid ad-free tier for ad-sensitive users. In this paper, we introduce the Generalized Ad-Supported Subscription (GAS) mechanism-a broad class consisting of subscription-fee and ad-intensity combinations that spans the entire spectrum from fully ad-supported to fully subscription-based access. Using the principles of mechanism design, we characterize a revenue-maximizing GAS mechanism and contrast it with ad-only, subscription-only, and the two-tier menu. Further, we estimate our model parameters and empirically validate our theoretical results in the context of Video-on-Demand platforms. Our analysis shows that the optimal GAS mechanism yields a substantially higher revenue than the ad-only and subscription-only mechanisms. More importantly, this additional revenue improvement does not come at the expense of consumer surplus-this shows that the GAS mechanism improves the overall economic pie by better matching user preferences.